MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN IMPROVING SERVICES AND QUALITY OF EDUCATION AT THE AL-AZHAR PAGERWOJO LEADING MADRASAH - Ma'mun, Sukron Ma'mun (Al-Mudarris: Journal Of Education, 2024)
Madrasah is an Islamic Educational Institution that is able to maintain its existence in carrying out its functions. Madrasah is also obliged to improve its quality to maintain its sustainability. Therefore, the management of facilities and infrastructure is aimed at improving the services of the madrasah. This study aims to describe the infrastructure management activities carried out by the Al-Azhar Superior Madrasah in order to improve education services and quality, what obstacles are faced in the implementation process, and solutions taken to anticipate existing obstacles. This research is qualitative in nature with the type of case study at the Al-Azhar Superior Madrasah. This research uses participatory observation methods, in-depth interviews and documentation studies in data mining. Data analysis uses the Miles, Huberman and Saldana techniques. The management of facilities and infrastructure at the Al-Azhar Superior Madrasah has been carried out quite well in terms of planning, procuring, maintaining, and inventorying the facilities and infrastructure in the madrasah environment, which has proven to be able to improve services which ultimately improve the quality of education, as evidenced by the increasing quality of its output. The constraints are that there is a lack of funds and administrative staff. The solutions that have been implemented by the Al-Azhar Superior Madrasah to solve the existing problems are: 1) Procurement must be in accordance with the Madrasah Work Plan that has been prepared, 2) Organization must be carried out in accordance with the madrasah's duties and functions, 3) Control of procurement and use of facilities and infrastructure must be carried out with previously decided procedures, so that supporting documents are complete. The role of each stakeholder determines the quality of education in terms of facilities and infrastructure at the Al-Azhar Superior Madrasah.